Pursuit Of An Ideal Model For Community Eye Health — Non-Governmental Organisations (NGOs) - Hnin, Hnin; Tan, Hui Yi; Agrawal, Kajal; Agrawal, Rupesh (Nepalese Journal of Ophthalmology, 2018)
Visual impairment is a crippling condition affecting quality of life and depriving patients of many opportunities. It is associated with increased mortality rates directly through occurrence of adverse events such as falls and impaired emotional well-being, and indirectly through visual impairment brought upon by systemic conditions such as diabetes and hypertension (Foong et al. 2008, Fong et al. 2014, Khanna et al. 2013, Song et al.2014, Wang et al. 1999). The number of patients suffering from reversible causes of blindness is substantial. In 2010, World Health Organisation estimates that 285 million (4.25%) of the world’s population is visually impaired, of which 39 million (14%) are blind. Approximately, 80% of the visual impairment is preventable. Notable causes of preventable blindness include cataracts (51%), glaucoma (8%), age-related macular degeneration (5%), corneal opacities (4%), trachoma (3%) and uncorrected refractive errors (3%) (WHO, 2015). These conditions can be easily diagnosed and treated by ophthalmologists if adequate resources are available. It is increasingly challenging for the ophthalmologists and current healthcare systems to meet the ever-expanding demands of patients with reversible causes of blindness.